Research on the Impact of Outlets’ Experience Marketing and Customer Perceived Value on Tourism Consumption Satisfaction and Loyalty - Dai, Jingyu; Zhao, Liang; Wang, Qiang; Zeng, Hailiang (Frontiers in Psychology, 2022)
The research object of this subject, through cooperation with Shanghai International Fashion Education Center, a fashion travel education institution, is a convenient sample for the members of its “Japan Fashion Travel Project,” using quantitative research methods and research tools for questionnaires. From the perspective of tourist shopping experience marketing, this paper studies the relationship among tourist marketing, value perception, shopping satisfaction, and customer loyalty to outlets, and discusses the recommendations for sustainable development of outlets.